1988
DOI: 10.1176/appi.psychotherapy.1988.42.4.574
|View full text |Cite
|
Sign up to set email alerts
|

On Compulsive Shopping and Spending: A Psychodynamic Inquiry

Abstract: Compulsive shopping and spending, an impulse disorder, form a specific psychodynamic complex with common developmental precursors of pathological narcissism. Compulsive shopping and spending are distinguished from other symptomatic uses of money and impulsive acts. Four cases illustrate some psychodynamic considerations and therapeutic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
11

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 177 publications
(77 citation statements)
references
References 0 publications
1
65
0
11
Order By: Relevance
“…Consumer behavior researchers have presented a variety of explanations for various abnormal consumption behaviors that support, parallel, or are subsumed by these three proposed categories. For example, researchers have studied physiological (e.g., neurological substrates: Faber et al, 1987;Krych, 1989), environmental (e.g., retail environment: Cobb & Hoyer, 1986;Tauber, 1972), social (e.g., socialization : Krueger, 1988;Magee, 19941, and psychological (e.g., personality: Hanley & Wilhelm, 1992) bases for excessive consumption behavior. Further support for these three factors are their similarity to those proposed by Fullerton and Punj (1993): consumer traits (sociopsychological) and predispositions (neuropsychogenetic) and characteristics of the exchange setting and marketing institutions (situational).…”
Section: Compulsive Consumption Mottvesmentioning
confidence: 99%
See 2 more Smart Citations
“…Consumer behavior researchers have presented a variety of explanations for various abnormal consumption behaviors that support, parallel, or are subsumed by these three proposed categories. For example, researchers have studied physiological (e.g., neurological substrates: Faber et al, 1987;Krych, 1989), environmental (e.g., retail environment: Cobb & Hoyer, 1986;Tauber, 1972), social (e.g., socialization : Krueger, 1988;Magee, 19941, and psychological (e.g., personality: Hanley & Wilhelm, 1992) bases for excessive consumption behavior. Further support for these three factors are their similarity to those proposed by Fullerton and Punj (1993): consumer traits (sociopsychological) and predispositions (neuropsychogenetic) and characteristics of the exchange setting and marketing institutions (situational).…”
Section: Compulsive Consumption Mottvesmentioning
confidence: 99%
“…Compulsive shopping (Krueger, 1988) has alternatively been labeled addictive buying (Krych, 1989;Scherhorn, 1990;Scherhorn, Reisch, & Raab, 19911, compulsive buying (d'Astous, 1990;d'Astous, Maltais, & Roberge, 1990;Faber et al, 1987); Faber & O'Guinn (1988,1989,1982, compulsive spending (Hanley & Wilhelm, 1992) and Oniomania (McElroy et al, 1991). Nataraajan and Goff (1992) indicated that terms such as spending, buying, and shopping have been used interchangeably; yet, as they indicate, distinctions between these various forms of aberrant consumer behavior exist.…”
Section: Compulsiw Buying Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…There are several case studies regarding the psychoanalytic treatment of compulsive buyers, 6 each emphasizing the importance of early life experiences. More recently, cognitive-behavioral models have been developed for CBD.…”
Section: Treatment 1) Psychotherapymentioning
confidence: 99%
“…6 Interest was revived in the early 1990s, when three independent clinical case series involving a total of 90 subjects were published. [7][8][9] The disorder has been described worldwide with reports coming from the US, Canada, 10 England, 5 Germany, 11 France, 12 and Brazil.…”
Section: Introductionmentioning
confidence: 99%